2019
DOI: 10.1210/clinem/dgz019
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fluid Proteins for Minimally Invasive Assessment of Endometrial Receptivity

Abstract: Context Clinically used endometrial (EM) receptivity assays are based on transcriptomic patterning of biopsies at midsecretory endometrium (MSE) to identify the possible displacement or disruption of window of implantation (WOI) in patients with recurrent implantation failure (RIF). However, biopsies are invasive and cannot be performed in the same cycle with in vitro fertilization embryo transfer, while uterine fluid (UF) analysis is considered minimally invasive and can immediately precede … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…These observations imply that the secretion of EVs would be hampered in the endometria of infertile women. Recently, the uterine fluid proteome of women with RIF and controls has been compared and several differentially abundant proteins were identified, some of which are associated with EVs 34 . Endometrial EVs modulated fertility is also evident from studies in dairy cows with divergent fertility.…”
Section: Extracellular Vesicles In Disorders Of Endometriummentioning
confidence: 99%
“…These observations imply that the secretion of EVs would be hampered in the endometria of infertile women. Recently, the uterine fluid proteome of women with RIF and controls has been compared and several differentially abundant proteins were identified, some of which are associated with EVs 34 . Endometrial EVs modulated fertility is also evident from studies in dairy cows with divergent fertility.…”
Section: Extracellular Vesicles In Disorders Of Endometriummentioning
confidence: 99%
“…Focusing on 25 exclusive sperm-interacting proteins from UF, to the best of the authors’ knowledge, few of these have been previously identified in boar and might play a role during fertilization. Regarding apolipoprotein-E, it was found in blood [ 46 ] and expressed in human endometrium during the proliferative phase [ 47 , 48 , 49 ]. Within the uterus, this protein is involved in cholesterol uptake, immune response, and preparing the endometrium for embryo implantation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another protein, belonging to the family of heat shock proteins, the heat shock 70-kDa protein 1-like, was detected in spermatozoa incubated with UF. This protein participates in several physiological processes (i.e., cell cycle, cell proliferation, and differentiation) and has been identified in UF from different species, such as human [ 47 , 58 ], equine [ 55 ], ovine [ 32 ], mouse [ 59 ], bovine, and porcine [ 60 ]. In particular, the binding of this protein to porcine and bovine spermatozoa during their journey from the uterus towards the oviduct avoids early capacitation and aids in the maintenance of sperm viability [ 59 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations